Malaysian economy : analysis of performance in 1990 and issues beyond / Annie Wong Muk Ngiik - Muk Ngiik, Annie Wong (Institut Teknologi MARA Cawangan Sarawak, 1991)
The Malaysian economy enjoyed a buoyant economic growth in 1990 despite signs of the onslaught of economic recession in the industrial nations. Real Gross Domestic Product grew at a high rate of 10%. This is the highest growth rate ever achieved by the country since 1976. when the growth rate was then 11.6 per cent. This remarkable performance of the economy was chiefly attributed to the strong domestic demand which contributed 13.6 per cent to the overall real GDP growth. The private sector played an important role in this surge in domestic demand. Private investment rose by about 31% in 1990, out of which a significant portion was direct foreign investment amounting to $13,317.1 million, representing an increase of about 60%. However, growth in merchandise export slowed down in in 1990 amidst falling economic growth in the industrialized nations.